Influence of ionizing radiation on the elemental content and structure of natural minerals - Dikiy, N.P.; Bereznyak, E.P.; Layshko, Yu.V.; Medvedeva, E.P.; Medvedev, D.V. (Problems of Atomic Science and Technology, 2022)
The granites of the Ukrainian crystalline shield and the Donetsk-Dnieper hollow of the Pre-Cambrian basement, discovered at a depth of 840…900 to 3420 m were irradiated on a KUT-1 linear electron accelerator with the following parameters: electron energy Е ≈ 7 MeV, average beam current I = 500 μA, temperature of the irradiated samples Т ∼ 40°С, absorbed dose Dₐᵦₛ = 10⁷ Gy. Gamma-activation analysis was used to determine the content of elements in the samples. The samples were irradiated by bremsstrahlung from the linear accelerator electron NSC KIPT with energy 23 MeV and current 500 μA. The structure and phase composition of samples were investigation by infrared spectroscopy in the frequency 400…4000 cm⁻¹. Crystal optical studies were carried out on polarizing microscope using immersion liquides. It is shown that high-energy electron irradiation of granites causes radiation-stimulated transformations in the structure and phase homogeneity of mineral. The most pronounced changes in biotites after high-energy electron irradiation of granites are manifested in a change in the color of biotite, apparently due to oxide phases Fe₂O₃ and Fe₃O₄. Considering the state of granites under radiation conditions it can be used for the immobilization and disposal of radioactive waste.